Teacher Identity and Sociopolitical and Professionalization Demands. An Analysis of Their Relation in Light of a New Systemic Paradigm: the Three-Dimensional Spiral of Sense - Aparicio, Miriam (European Journal of Social Science Education and Research, 2020)
This research has been done in the field of Education, Sociology and Social and Organizational Psychology and forms part of a larger complementary research program. We cite: 1) Studies carried out with secondary level and university educators seeking to contrast psychosocial and other factors related to teacher training that influence teaching practice and teaching identity, versus feelings of failure, burnout and fatalism. 2) Research with teachers from different countries (Argentina, Spain, France and Paraguay) seeking to observe the weight that the macro-context has on issues that both teachers and their institutions face at the micro-level. 3) Currently, we are continuing this research, though this time analyzing the shared representations that university students have of the most urgent problems their professors face. The methodology utilized was quantitative-qualitative: questionnaires, semi-structured surveys including open phrases which allowed actors to speak freely and, in the case of the French-Argentine research with .with IUFM professors, a special qualitative technique was applied: hierarchical evocation. This allowed us to determine which aspects related to professional pathways (objective and subjective) formed part of the “core” of social or shared representations and which were secondary aspects at the periphery of said core. Our findings show non-linear relationships between study variables – Expectations, Satisfaction and Achievement – and self-sustained interplay along three levels: micro individual, meso organizational and macro social. These are interpreted in light of a new systemic paradigm in human and social sciences: “The Three-Dimensional Spiral of Sense”.
Keywords: Teacher Identity – Professional Achievement – Expectations – Satisfaction – New Paradigm I.